Law Enforcement Against Trafficking of Narcotics & Prohibited Drugs in Pohuwato District - Alhasni, Mohamad Rizky; Beddu, Sumiyati; Nur, Rafika (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2024)
Drug abuse from year to year always increases, The causes of this abuse consist of two factors, namely internal and external factors. With these problems, this study aims to determine the implementation of law enforcement against drug abuse and illegal drugs. The approach method that the author will use in this study is the Juridical Sociological approach method. The Juridical Sociological approach focuses on the implementation of research to obtain empirical legal knowledge by being directly involved with the object. The results of the study show that in the process of law enforcement against narcotics crimes both in the process of investigation, investigation, prosecution, examination in court and the execution process refers to the Criminal Procedure Code (KUHAP) while the imposition of sanctions is regulated in Law Number 35 of 2009 concerning Narcotics. BNN, Police, Prosecutors, Judges and other law enforcers including community components have the responsibility to carry out prevention and control of drug abuse. This is a mandate from the laws and regulations, including in this case the Narcotics Law. Prevention of drug abuse must be carried out as soon as possible with anticipatory measures, including primary prevention, secondary prevention, and tertiary prevention